(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper we introduce and study new class of homeomorphisms called Ng-homeomorphisms (nano g-homeomorphismss) in nano topological spaces and certain properties are investigated. We also investigate the concept of nano g- homeomorphisms and discussed their relationships with other forms of nano sets. Further, we show that the set of all Ng-homeomorphisms form a group under the operation composition of mappings.